Highly transparent, UV‐B protective Al–Zn–O films with potential application in greenhouse screen systems. Issue 3 (28th January 2019) - Kosari Mehr, Abbas; Hantehzadeh, Mohammad Reza; Darabi, Elham
Abstract: Extremely thin, Al–Zn–O composite films (21 ± 6 nm) are deposited on fused silica substrates under various percentages of oxygen in the oxygen/argon gas mixture (3%, 4.5%, 6%, and 7.5%). The films are prepared by a cylindrical DC magnetron sputtering system, utilizing a single compound target. The effects of the oxygen percentage on the compositional, morphological, and optical properties of the films are investigated by energy‐dispersive X‐ray spectroscopy, scanning electron microscopy, UV‐visible spectrophotometry, and atomic force microscopy. The chemical composition of the films is Al1 Zn1+X O with 0.2 < X < 1. The average visible transmittance of 93.6% with a high level of uniformity is obtained when the sputtering deposition performs under the oxygen percentage of 6%. It is found that the optical band gap of the films can be tailored toward higher energy by increasing oxygen percentage; however, the adjustable range is not so significant. The results offer cost‐efficient films with high, uniform transmittance in the visible region and with an ability to attenuate more than 10% of incident UV‐B radiation (280‐315 nm). This type of films can potentially be included in greenhouse screen systems to effectively protect the plants from the elevated UV‐B radiation without altering natural conditions. Abstract : The greenhouses including the Al‐Zn‐O ceramic coatings in the design of their screen systems effectively protect the plants from the elevated UV‐B radiation caused by man‐made ozone layer depletion.